Personality, opinion strength, and social media use – not such a straightforward relationship - Melissa Cox; Bernadine Cocks; Susan E. Watt; Elizabeth C. Temple (Australian Journal of Psychology)
Objective This study investigated the link between personality, opinions on social and political issues, and social media use, as well as the moderating effects of social media use on the relationship between personality and those opinions. Past research suggests that personality, opinion direction (i.e. favourability of an issue), and social media use are inter-related. However, the relationship between personality and opinion strength (i.e. how extreme an opinion is disregarding favourability), and potential moderating effects of social media use on that relationship have yet to be investigated.Method Participants (N = 536) completed surveys measuring social media usage, personality, and opinions on various social issues.Results Several personality traits predicted opinion direction or strength on at least one social issue. When all social issues were combined to measure overall progressive opinions, openness and extraversion predicted opinion direction, and openness predicted opinion strength. Time spent on social media significantly predicted direction of opinions on several issues, as well as strength of opinion on the issue of gender equality, however it did not moderate any relationship between personality and opinion direction or strength.Conclusions Although opinions, personality, and social media use are sometimes related, individuals high or low in particular personality traits are at no greater risk of polarising due to social media use than anyone else.